A tailored and red-emissive type I photosensitizer to potentiate photodynamic immunotherapy. Issue 39 (12th September 2022) - Zhou, Sirong; Li, Ruipeng; Li, Ying; Wang, Yunxia; Feng, Liheng
Abstract : A tailored type I PS for imaging-guided photodynamic immunotherapy is developed. The work enhances the killing effect of PDT against hypoxic solid tumors and boosts the T-cell immune response to residual and metastasis tumor cells. Abstract : Photodynamic immunotherapy (PDIT) has emerged as a technique which shows great potential in eradicating malignant tumors due to its advantages of simultaneously damaging primary tumors and inhibiting tumor metastasis and recurrence. However, the hypoxic microenvironment of tumor tissue and immune escape are two major challenges that PDIT faces. Hence, a well-designed water-soluble type I photosensitizer (TbT-TPP) based on a "D–A" strategy is reported for imaging-guided PDIT. The enhanced dihedral angle, prolonged conjugation length, strong electron withdrawing effect, and electron-rich condition endow TbT-TPP with a superior type I ROS generation ability and aggregation-induced red emission, which is demonstrated by comparision with the control molecule. We demonstrate that in hypoxic tissue, TbT-TPP can light up tumors and further efficiently kill them, triggering immunogenic cell death by generating type I ROS, which sequentially promotes the maturation of dendritic cells and enhances the T-cell response to tumor cells. Combined with immune adjuvant R837, TbT-TPP based-PDIT achieves the complete elimination of solid tumors and inhibition of tumor metastasis of living mice. This work provides a potential theranostic material and new insights into the improvement of PDIT against hypoxic tumors.